A study of the deuterium isotope effect on zinc(II) hydrolysis and solubility under hydrothermal conditions using density functional theory. (8th June 2022) - Conrad, Jacy K.; Tremaine, Peter R.
Highlights: Lowest energy configurations of hydrated zinc hydroxide complexes. Theoretical zinc hydrolysis constants in light and heavy water at 25 °C and 250 °C. Estimated solubility curves for ZnO(s) in heavy water as a function of pD. Abstract: Density functional theory (DFT) calculations at the B3LYP/6-311++G(d, p) level of theory were used to determine the lowest energy configurations of the hydrolysis species of aqueous zinc hydroxides in light and heavy water under ambient and hydrothermal conditions. The species geometries were optimized in the Polarizable Continuum Model (PCM) with the addition of up to 6 explicit solvent molecules. The structures of the light water species agreed well with experimental results and computational results reported in other studies. The equilibrium constants were computed for each of the hydrolysis reactions and the predicted values were on the same order of magnitude as experimental values. The deuterium isotope effect on the hydrolysis constants, Δ p K = - Δ log K = log K H - log K D, was calculated and combined with critically evaluated light water equilibrium constants to provide an estimate of the hydrolysis reaction constants in heavy water at 25 °C and 250 °C. A semi-empirical expression was derived for predicting the difference in the solubility of ZnO(s) in heavy water relative to that in light water. Thermochemical data for the hydrolysis reactions of Zn 2+ in heavy water at elevated temperatures are of interest for modelling activated corrosion product transport and the potential use of zinc additions in the primary coolant of pressurized heavy water nuclear reactors.